Perspectives on the microorganisms with the potentials of PET-degradation - Liu, Xiao-huan; Jin, Jun-li; Sun, Hai-tong; Li, Shuo; Zhang, Fei-fei; Yu, Xin-hong; Cao, Qi-zhi; Song, Yu-xuan; Li, Nan; Lu, Zhen-hua; Wang, Tao; Liu, Fei; et al. (Frontiers in Microbiology, 2025)
Polyethylene terephthalate (PET), a widely used synthetic polymer in daily life, has become a major source of post-consumer waste due to its complex molecular structure and resistance to natural degradation, which has posed a significant threat to the global ecological environment and human health. Current PET-processing methods include physical, chemical, and biological approaches, however each have their limitations. Given that numerous microbial strains exhibit a remarkable capacity to degrade plastic materials, microbial degradation of PET has emerged as a highly promising alternative. This approach not only offers the possibility of converting waste into valuable resources but also contributes to the advancement of a circular economy. Therefore in this review, it is mainly focused on the cutting-edge microbial technologies and the key role of specific microbial strains such as Ideonella sakaiensis 201-F6, which can efficiently degrade and assimilate PET. Particularly noteworthy are the catalytic enzymes related to the metabolism of PET, which have been emphasized as a sustainable and eco-friendly strategy for plastic recycling within the framework of a circular economy. Furthermore, the study also elucidates the innovative utilization of degraded plastic materials as feedstock for the production of high-value chemicals, highlighting a sustainable path forward in the management of plastic waste.